The PERANAN CITRA MEREK, KUALITAS PRODUK, DAN KEPUASAN KONSUMEN PADA LOYALITAS KONSUMEN SMARTPHONE MEREK APPLE - Ferro Satria Tanzil; Allen Kristiawan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The advancement of technology has greatly progressed in the current global era. There are numerous brands on the market such as Apple, Samsung, Oppo, and others. The use of Apple products in Indonesia itself is highly favored by the public due to the brand's reputation, quality, and satisfaction, leading to customer loyalty. The objective of this research is to test and analyze the role of brand image, product quality, and customer satisfaction in customer loyalty. The research method employed in this study is purposive sampling, where questionnaires were distributed to 200 respondents. The sample consists of individuals who use Apple smartphones. After collecting the data, validity tests and reliability tests, as well as classical assumption test multicollinearity and heteroscedasticity and multiple linear regression tests will be conducted. The results of the tests indicate a positive impact of brand image, product quality and customer satisfaction on customer loyalty.